2018
DOI: 10.1039/c8ew00386f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sludge reduction and biogas generation in high-rate anaerobic side-stream reactors for wastewater treatment

Abstract: Activated sludge systems incorporating a 2 day anaerobic side-stream reactor (ASSR) show significantly decreased waste sludge production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…For the continuous production of biogas and the stability of the process, each parameter should be within the prescribed limit. A small fluctuation in a single parameter results in the instability of the entire AD process (Park et al 2018). In the first digester, the methane yield for cow dung, indicated by line A, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the continuous production of biogas and the stability of the process, each parameter should be within the prescribed limit. A small fluctuation in a single parameter results in the instability of the entire AD process (Park et al 2018). In the first digester, the methane yield for cow dung, indicated by line A, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Food and energy are the basic needs of mankind. Due to the rapid increase in the world population and the high dependence on fossil fuels, developing countries have had a significant part in greenhouse gas emissions and environmental pollution (Park et al 2018). Due to the limited resources of oil, gas, coal, and the abrupt fluctuation in their prices, developing countries have serious problems in their energy sectors (Bhoite and Vaidya 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, very little published information is available about the effect of ASSR installation in a WWTP. In a previous study, the authors observed an increase in the BMP of excess sludge from an ASSR operating with an HRT of 2 days under mesophilic conditions [15]. In that study, the ASSR was inserted in the activated sludge return line of a CAS system consisting of a primary clarifier followed by an aeration basin and a secondary clarifier.…”
Section: Methane Production Yield In Excess Sludge From Osa and Casmentioning
confidence: 97%
“…Another reason why the OSA process could involve an increase of methane productivity is related to the higher bacterial diversity of the ASSR sludge compared with the activated sludge of the control system [36]. Park and co-authors [15] supposed that the sludge from a mesophilic ASSR contained key anaerobic communities, thus the addition of this sludge to anaerobic digesters provided anaerobic seed that enhanced the speed of anaerobic digestion.…”
Section: Methane Production Yield In Excess Sludge From Osa and Casmentioning
confidence: 99%
See 1 more Smart Citation